Problematika Kinerja Pustakawan di Perpustakaan Universitas Negeri Padang - Annisa, Fitra Febri; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This paper aims to identify and describe: (1) the performance of librarians in managing libraries in Padang State University Library; (2) the efforts made in improving the performance of librarians in managing libraries in Padang State University Library; (3) the constraints faced by librarians in managing libraries in Padang State University Library. This type of research is used in this paper is a qualitative research method used is descriptive method. Data were collected through direct observation of interviews with librarians Library Unit Padang State University.Based on the results of the research, concluded the following: first the performance of the librarian is not maximized on credit scoring to be met in order for a promotion and librarian positions; second collection of Padang State University Library inadequate; three infrastructure Padang State University Library were inadequate. Keywords : school librarian, guidance, expand ability.